Living by Inches : The Smells, Sounds, Tastes, and Feeling of Captivity in Civil War Prisons - Kutzler, Evan A. (Book collections on Project MUSE., 2019)
From battlefields, boxcars, and forgotten warehouses to notorious prison camps, prisoners seemed to be everywhere during the American Civil War. 'Living by Inches' examines how imprisoned men in the Civil War perceived captivity through the basic building blocks of human experience - their five senses.